Do Babies Matter? : Gender and Family in the Ivory Tower - Mason, Mary Ann; Goulden, Marc; Wolfinger, Nicholas H., 1966- (Book collections on Project MUSE., 2013)
The generation of scholars in the early twenty-first century differs in many ways from its predecessor of just a few decades ago. Academia once consisted largely of men in traditional single-earner families. Now, men and women fill the doctoral student ranks in nearly equal numbers and most will experience both the benefits and challenges of living in dual-income households. This generation also has different expectations and values, notably the desire for flexibility and balance between careers and other life goals. However, changes to the structure and culture of academia have not kept pace with young scholars' desires for work-family balance. This is a comprehensive examination of the relationship between family formation and the academic careers of men and women. The book begins with graduate students and postdoctoral fellows, moves on to early and mid-career years, and ends with retirement. Individual chapters examine graduate school, how recent PhD recipients get into the academic game, the tenure process, and life after tenure. The authors explore the family sacrifices women often have to make to get ahead in academia and consider how gender and family interact to affect promotion to full professor, salaries, and retirement. Concrete strategies are suggested for transforming the university into a family-friendly environment at every career stage. The book draws on over a decade of research using unprecedented data resources, including the Survey of Doctorate Recipients, a nationally representative panel survey of PhDs in America, and multiple surveys of faculty and graduate students at the ten-campus University of California system.